Electrospinning of Cyclodextrin Nanofibers: The Effect of Process Parameters. (15th June 2020) - Topuz, Fuat; Uyar, Tamer
Abstract : Cyclodextrin (CD) nanofibers have recently emerged as high-performance materials owing to their large surface area-to-volume ratio, along with the presence of high active CD content for their applications in drug delivery and water treatment. Even though there are several studies on the polymer-free electrospinning of CD molecules of different types, the effects of electrospinning process parameters on the morphology and diameter of the resultant fibers have not addressed yet. In this study, the influence of electrospinning process variables on the morphology and diameter of the resultant CD nanofibers is systematically studied using two different solvent systems, i.e., water and N, N-dimethylformamide (DMF). On adjusting the electrospinning process parameters (i.e., electrical field, flow rate, tip-to-collector distance (TCD), and needle diameter), uniform CD nanofibers could be produced from aqueous and DMF solutions. Generally, the electrospinning of thicker fibers was observed by increasing the applied voltage and flow rate due to higher mass flow. Increasing TCD boosted the fiber diameter. Likewise, the use of needles with larger diameters resulted in the electrospinning of thicker fibers from DMF solutions, which might be attributed to higher viscosity due to reduced shear rate.